1995
DOI: 10.1111/1523-1747.ep12613469
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus IgG, but Not Bullous Pemphigoid IgG, Causes a Transient Increase in Intracellular Calcium and Inositol 1,4,5-Triphosphate in DJM-1 Cells, a Squamous Cell Carcinoma Line

Abstract: It is still unclear what kinds of mechanisms are involved in blister formation after antibodies bind to the antigens in pemphigus and bullous pemphigoid. The effects of IgGs from pemphigus vulgaris, pemphigus foliaceus, and bullous pemphigoid sera on intracellular calcium concentration ([Ca++]i) and inositol 1,4,5-trisphosphate were examined in a human squamous cell carcinoma cell line (DJM-1 cells) and in cultured human keratinocytes to clarify whether signal transduction via calcium is involved. IgGs were pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0
1

Year Published

1997
1997
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(72 citation statements)
references
References 28 publications
5
66
0
1
Order By: Relevance
“…64 An increase of calpain activity in keratinocytes treated with PVIgGs observed in this study is in keeping with observations that binding of PVIgG to keratinocytes causes a transient increase in intracellular free Ca 2ϩ , activates phospholipase C, stimulates production of inositol 1,4,5-trisphosphate, induces activation and translocation of protein kinase C from the cytosol to the particulate/cytoskeleton fractions, and increases the phosphorylation status of cellular proteins. 4,30,[65][66][67][68][69][70] Furthermore, it has been recently reported that inhibitors of tyrosine kinases, phospholipase C, calmodulin, and the serine/threonine kinase protein kinase C prevented PVIgG-induced acantholysis in vivo. 71 TNF-␣ has been shown to activate calpains because of a rise in the concentration of intracellular free Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…64 An increase of calpain activity in keratinocytes treated with PVIgGs observed in this study is in keeping with observations that binding of PVIgG to keratinocytes causes a transient increase in intracellular free Ca 2ϩ , activates phospholipase C, stimulates production of inositol 1,4,5-trisphosphate, induces activation and translocation of protein kinase C from the cytosol to the particulate/cytoskeleton fractions, and increases the phosphorylation status of cellular proteins. 4,30,[65][66][67][68][69][70] Furthermore, it has been recently reported that inhibitors of tyrosine kinases, phospholipase C, calmodulin, and the serine/threonine kinase protein kinase C prevented PVIgG-induced acantholysis in vivo. 71 TNF-␣ has been shown to activate calpains because of a rise in the concentration of intracellular free Ca 2ϩ .…”
Section: Discussionmentioning
confidence: 99%
“…Pemphigus antibodies were initially thought to disrupt Dsg trans-interaction but later have been shown to also exert their pathological effects by triggering intracellular signaling pathways Seishima et al, 1995). Direct steric inhibition apparently mimics the so-called tryptophan-swap between interacting Dsg3 molecules which hampers cis-and trans-interaction (Di Zenzo et al, 2012;Spindler et al, 2013;Yamagami et al, 2010).…”
Section: Role Of Signaling Induced By Autoantibodies In Pemphigus Patmentioning
confidence: 99%
“…Many signaling molecules have been associated with pemphigus pathogenesis and shown to contribute to loss of cell adhesion in a variety of model systems (Getsios et al, 2010;Waschke, 2008). These include phospholipase C, Ca 2 ϩ , and protein kinase C (PKC) Osada et al, 1997;Seishima et al, 1995) as well as plakoglobin regulating the expression of Myc (Caldelari et al, 2001;Williamson et al, 2006). Rho GTPases act as molecular switches in actin dynamics (Gliem et al, 2010;Waschke et al, 2006).…”
Section: Role Of Signaling Induced By Autoantibodies In Pemphigus Patmentioning
confidence: 99%
“…Proposed mechanisms for PV IgG-induced keratinocyte detachment include (a) proteinase activation, (b) steric hindrance, and (c) activation of transmembrane signaling that down-regulates cell-cell adhesion (7)(8)(9)(10)(11). Previous work has suggested that PV IgG may activate intracellular signaling events; however, the precise nature and biological consequences of these events and their relationship to the mechanism of PV IgG-induced acantholysis remain unknown (7,8).…”
mentioning
confidence: 99%
“…Previous work has suggested that PV IgG may activate intracellular signaling events; however, the precise nature and biological consequences of these events and their relationship to the mechanism of PV IgG-induced acantholysis remain unknown (7,8). The specificity of anti-dsg3 antibodies in PV patient sera enabled us to utilize this reagent to initiate changes in desmosome structure and look for activation of signaling and the relationship of these signaling events to the mechanism of acantholysis.…”
mentioning
confidence: 99%